2015
DOI: 10.1515/med-2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug interactions with statins: Estonian register-based study

Abstract: In Estonia, HMG-CoA reductase inhibitors are widely used to modify lipid levels but there are no current data on additional medicines prescribed alongside the statins. The aim of this study was to identify the frequency of potential clinically relevant interactions at a national level among an outpatient population treated with statins between January and June 2008, based on the prescription database of the Estonian Health Insurance Fund. This retrospective prevalence study included 203,646 outpatients aged 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(36 reference statements)
1
6
1
Order By: Relevance
“…These results suggest that rucaparib increased the exposure to oral contraceptives mostly through inhibiting their elimination. There were also 2 patients in Arm B who were taking atorvastatin, which, like other statins, has been reported to weakly increase exposure to oral contraceptives [25]. Although the oral contraceptive exposure ratios of these 2 patients were consistent with the exposure ratios of other patients who were not on statin therapy (data not shown), the effect of atorvastatin may not have been apparent as these patients were on stable doses of atorvastatin throughout the study.…”
Section: Discussionmentioning
confidence: 75%
“…These results suggest that rucaparib increased the exposure to oral contraceptives mostly through inhibiting their elimination. There were also 2 patients in Arm B who were taking atorvastatin, which, like other statins, has been reported to weakly increase exposure to oral contraceptives [25]. Although the oral contraceptive exposure ratios of these 2 patients were consistent with the exposure ratios of other patients who were not on statin therapy (data not shown), the effect of atorvastatin may not have been apparent as these patients were on stable doses of atorvastatin throughout the study.…”
Section: Discussionmentioning
confidence: 75%
“…High numbers of comorbidities (hypertension [25], hyperlipidemia [26], diabetes mellitus [27], chronic kidney disease [28], arrhythmia [29], heart failure [30], epilepsy [31] significantly affected the frequency of pDDIs in previous studies. A high frequency of pDDIs was registered in patients with cardiac disorders, up to 91.6% [32] which was similar to our results where a large percentage of patients had cardiac comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the study design, population and setting from 4.6% to 36.6% of statin-treated patients may be exposed to statin pDDIs (Egger et al, 2007;Rätz Bravo et al, 2005;Gavronski et al, 2015;Samardzic, Benkovic, Vrca, 2017;Morival et al, 2018). Up to now, only a handful of studies assessed risk factors for statin pDDIs mostly in outpatients (Egger et al, 2007;Rätz Bravo et al, 2005;Gavronski et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the study design, population and setting from 4.6% to 36.6% of statin-treated patients may be exposed to statin pDDIs (Egger et al, 2007;Rätz Bravo et al, 2005;Gavronski et al, 2015;Samardzic, Benkovic, Vrca, 2017;Morival et al, 2018). Up to now, only a handful of studies assessed risk factors for statin pDDIs mostly in outpatients (Egger et al, 2007;Rätz Bravo et al, 2005;Gavronski et al, 2015). In a study conducted in Switzerland, risk factors for statin pDDIs in ambulatory statin-treated dyslipidaemic patients were Ana V. Pejčić, Slobodan M. Janković, Goran Davidović number of drugs, cardiac failure, arrhythmias and being a patient from the French-speaking part of Switzerland (Rätz Bravo et al, 2005), while analysis of the data from this study according to different age groups have shown that male sex, number of pharmaceutical preparations prescribed and psychiatric disorders were risk factors in patients ≤54 years, whereas in ≥55-year-old patients risk factors were number of pharmaceutical preparations or pharmacologically active substances prescribed and a diagnosis of arrhythmia or heart failure (Egger et al, 2007).…”
Section: Introductionmentioning
confidence: 99%